2014
DOI: 10.1177/0886260513516006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Substance Use and Intimate Partner Violence in a Sample of A/PI MSM

Abstract: This study evaluates the prevalence of three forms of intimate partner violence (IPV) (i.e., experience of physical, psychological/symbolic, and sexual battering) among a national sample of Asian/Pacific Islander (A/PI) men who have sex with men (MSM) in the United States and identifies their characteristics. The study also reports the differences of substance use behavior between MSM with and without a previous history of IPV. Our sample was recruited through venue-based sampling from seven metropolitan citie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
16
0
2
Order By: Relevance
“…In our study, 29% (74 out of 257) of never-tested men at follow-up had experienced IPV. We found that several types of IPV were positively associated with post-intervention testing, which was consistent with a previous study in the U.S. showing similar associations [25]. They were also positively associated with HIV diagnosis [17].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 29% (74 out of 257) of never-tested men at follow-up had experienced IPV. We found that several types of IPV were positively associated with post-intervention testing, which was consistent with a previous study in the U.S. showing similar associations [25]. They were also positively associated with HIV diagnosis [17].…”
Section: Discussionsupporting
confidence: 92%
“…Houston and McKirnan (2007) noted that abused men in the Chicago area were more likely to report frequent use of substances before or during sex. Other studies identified a relationship between IPV and drug use in other samples of MSM (Bimbi et al, 2008;Hughes et al, 2010;Klitzman et al, 2014;Koblin et al, 2006;Nieves-Rosa, Carballo-Dieguez, & Dolezal, 2000;Tran et al, 2014;Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While few studies have examined relationships between experiences of IPV and health behaviors among MSM, there is evidence that supports a relationship between experiences of IPV and the increased use of a variety of substances (Bimbi, Palmadessa, & Parsons, 2008; Finneran & Stephenson, 2013; Hughes, McCabe, Wilsnack, West, & Boyd, 2010; Klitzman, Pope, & Hudson, 2014; Stults, Javdani, Greenbaum, Kapadia, & Halkitis, 2015; Tran et al, 2014; Wu et al, 2015). Welles, Corbin, Rich, Reed, and Raj (2011), for example, reported that MSM experiencing IPV as a victim were more likely to have consumed alcohol to intoxication in the preceding month.…”
mentioning
confidence: 99%
“…However, the same study found that cocaine use was statistically significantly associated with lifetime partner violence but not partner violence in the past month. Tran et al found that substance use, including ecstasy, cocaine, and methamphetamine use, was also linked to partner violence among Asian/Pacific Islander MSM [49]. The lack of statistically significant associations between substance use as a binary variable and disclosure-associated partner violence could have been due to the small cell sizes as a result of the small number of participants reporting verbal and/or physical abuse associated with disclosure in the past 30 days.…”
Section: Discussionmentioning
confidence: 99%